Structural MRI correlates of cognitive and neuropsychiatric symptoms in Long COVID: a pilot study - Joshi, Shantanu H.; Siddarth, Prabha; Lavretsky, Helen (Frontiers in Psychiatry, 2024)
Approximately 7% of COVID-19 patients (1.3% children) have exhibited symptoms of post-acute sequelae of SARS-CoV-2 infection (PASC), or Long COVID, and 20% of those present with neuropsychiatric symptoms. While a large number of MRI-based neuroimaging studies in this population have shown cortical atrophy in terms of gray matter volume and cortical thickness in patients, there is a growing body of work showing brain volume enlargements or thickness increases in patients compared to COVID negative controls. To investigate this further, we used structural magnetic resonance imaging (MRI) to examine differences in gray matter thickness for the cortical limbic and the dorsolateral prefrontal cortical regions between patients with Long COVID and healthy controls. Results showed increased cortical thickness in the caudal anterior, isthmus, and the posterior cingulate gyrus as well as the rostral middle frontal gyrus respectively along with higher gray matter volume in the posterior cingulate and the isthmus cingulate in patients with Long COVID. Cortical thickness and gray matter volumes for regions of interest (ROIs) were also associated with the severity measures, clinical dementia rating, and anxiety scores in the Long COVID group. Our findings provide supporting evidence for cortical hypertrophy in Long COVID.